A Physician in the Sphere of Artificial Intelligence: An Active Subject or Passive? - Dmitri A. Izutkin (Гуманитарный вектор)
The relevance of the article is associated with the influence of digital technologies on the medical sphere in the context of the formation of VUCA (variability, uncertainty, complexity, ambiguity) of the space. The main problem in this context is the ethical and philosophical aspects of the introduction of artificial intelligence (AI) in the medical field and the activities of the doctor, in particular, the possibility of its application in the diagnostic process. The latter is considered as an integral attribute of the cognitive nature of the medical profession. This is due to the constant and dynamic knowledge of the functioning of the human body in a state of normality and pathology, the problem of medical errors, as well as the philosophical reflections of the physician during the establishment of the diagnosis. The main goal is to show the contradictory nature of AI use in medicine, which is associated with certain qualitative transformation and reassessment of traditionally formed ideas about the role of the physician as an active subject within the framework of his professional activity. The methodology for studying this problem is based on a dialectical approach. This allows to consider the medical sphere as a synthesis and contradiction of the natural and artificial, as well as to emphasize the subject-object nature of the physician’s activity. The novelty of the study lies in the ethical and philosophical understanding of the self-identification of the physician and his clinical thinking in the conditions of the application of AI in medicine. In the context of this article, self-identification of a physician is understood as an awareness of his self and claim to be demanded in the field of medical professional activity; clinical thinking ‒ as a set of theoretical knowledge, practical skills, empirical experience and philosophical generalizations in an effort to identify and explicate the pathological process. It is emphasized that AI application significantly modifies the role and functions of the physician in modern (primarily clinical) medicine, which, in turn, affects his judgments about the disease (its etiology, psychosomatic nature, risk factors for health). This, in particular, is being stipulating in the communication of the physician with the patient. The prospects of the study are associated with further introduction of AI in clinical medicine, which is associated with the need to solve a complex of ethical and legal problems and the formation of a new medical paradigm.